Implementasi Teori Organisasi Berbasis Nilai Spiritual Islami dalam Praktik Pendidikan - Nurul Hidayati Murtafiah; Ismun Ali (Departement of Mathematics Education, 2023)
The implementation of Islamic spiritual values-based organizational theory in educational practices is an interesting concept to be used as a guideline in managing educational institutions. This concept combines modern organizational theory principles with Islamic spiritual values to create a quality, conducive, and dignified learning environment. This article discusses the basic concepts of organizational theory, the principles of Islamic spiritual values-based organizational theory, as well as education practices based on Islamic spiritual values. In addition, this article also explains the benefits of implementing Islamic spiritual values-based organizational theory in educational practices, such as producing students with strong character, improving the moral quality of students, increasing students' social awareness, enhancing teaching effectiveness, increasing teacher job satisfaction, and improving the reputation of educational institutions. By applying the concept of Islamic spiritual values-based organizational theory in educational practices, educational institutions can improve the quality of education, create a conducive learning environment, and produce a generation with strong character and high moral qualities.